What The Adolescence Do When They Get Financial Advice from Parent? (The Mediating Role of Financial Knowledge) - Satrio Tegar Gunung Koraag; Muhammad Irfan Mu'afi, S.E, M.A.B.; Virginia Ayu Sagita (Jurnal Paradigma, 2026)
This study investigates the influence of parental financial teaching on students’ financial behavior, with financial literacy serving as a mediating factor. An online survey was administered to 250 undergraduate students at Universitas Pembangunan Nasional “Veteran” Yogyakarta. The instrument gathered data on demographic characteristics, parental financial teaching, financial literacy, and financial behavior. Structural equation modeling was employed to test four hypotheses concerning the associations among these variables. The results reveal that financial literacy significantly and positively affects financial behavior. Moreover, parental financial teaching positively influences financial behavior both directly and indirectly through financial literacy, which functions as a mediator. These findings underscore the critical role of family financial education and financial literacy in shaping students’ financial practices. The study highlights the potential of implementing integrated educational initiatives that combine family-centered financial instruction and formal literacy programs to improve financial well-being among young adults. Nonetheless, the research is limited to a single institution and a relatively small sample size. Future studies are encouraged to expand the sample and incorporate additional variables to provide a more comprehensive understanding of the relationship between parental financial teaching, financial literacy, and financial behavior.